2016
DOI: 10.1515/iss-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts of interest in randomised controlled surgical trials: systematic review and qualitative and quantitative analysis

Abstract: Conflicts of interest may lead to biased trial designs and unbalanced interpretation of study results. We aimed to evaluate the reporting of potential conflicts of interest in full publications of surgical randomised controlled trials (RCTs). A systematic literature search was performed in CENTRAL, MEDLINE and EMBASE (1985–2014) to find all surgical RCTs of medical devices and perioperative pharmacological or nutritional interventions. The information on conflicts of interest was evaluated both quantitatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…A conflict of interest is present when a researcher or clinician involved in the trial has a personal interest that could bias the conduct or reporting of trial (Probst et al . 2016). Hence, a conflict of interest statement must be reported or, if none exists, the authors should explicitly state this fact in the manuscript.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…A conflict of interest is present when a researcher or clinician involved in the trial has a personal interest that could bias the conduct or reporting of trial (Probst et al . 2016). Hence, a conflict of interest statement must be reported or, if none exists, the authors should explicitly state this fact in the manuscript.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Although 144 years old, the GSS is a young and modern surgical society focusing on the interests of its members and the purposes of modern surgery for the best available surgical care. In this respect, the GSS supports the claim for transparency, which is also crucial for randomized controlled surgical trials, as it is reported in the first article submitted to and published in Innovative Surgical Sciences [7]. We are sure that open access will ultimately change the current approach of scientific evaluation [8], [9], [10].…”
mentioning
confidence: 54%
“…The presence of a conflicting interest, financial or otherwise, is likely to affect the validity of the trial and should be disclosed for the end‐user to understand that a conflict exists and make their own decision on its relevance (Probst et al . 2016). For example, a person who developed a new instrument, will inevitably be biased in favour of their own instrument when evaluating its effectiveness. Confounding bias ‐ The presence of various factors not considered as independent factors in a trial, but which may have an impact on the outcome of the trial.…”
Section: Glossary Listmentioning
confidence: 99%